Portlandia. Season one - Krisel, Jonathan; Armisen, Fred, 1966-; Brownstein, Carrie; Buscemi, Steve (Toronto, Ont. : Video Services Corp., 2011)
A series of short comedy sketches which are centered around the fictitious town of Portlandia and 1990s pop culture.
Farm -- A song for Portland -- Aimee -- Mayor is missing -- Blunderbuss -- Baseball.
Features: blooper reel; extended scenes; deleted scenes; season two preview; Fred Armisen speaks to OES Graduates; Thunderant videos; Fred, Carrie and Jonathan commentary over all six episodes.
Fred Armisen, Carrie Brownstein, Steve Buscemi, Jason Sudekis, Ellen Bloodworth.
Not rated.
Blu-ray disc, Dolby digital stereo.
This is a Blu-ray disc which can only be played on Blu-ray disc players and will not play on standard DVD players.
Keywords: Popular culture -- United States -- Humor -- Drama; Nineteen nineties -- Humor -- Drama; Sketch comedy television programs; Fiction television programs